Nutritional properties of some browse species used as goat feed in Pastoral dry lands, Uganda - Nsubuga, David; Nampanzira, Dorothy K.; Masembe, Charles; Muwanika, Vincent B. (Agroforestry Systems, 2020)
The nutritional properties of leaves of ten browse species commonly used as goat feed in pastoral drylands of Uganda were evaluated by determining their chemical composition and in vitro gas production. Dry matter (DM) content ranged between 896 and 914 g kg-1 DM and was not significantly different (P[0.05) among the browse species. There was a wide variation in the crude protein (CP) content of the browse species. The highest CP values were observed in Acacia compylacantha, Acacia fruiticosa and Acacia senegal, with 365, 247 and 245 g kg-1 DM respectively, while the lowest was observed in Ganisa similis (150 g kg-1 DM). The NDF values were highest in A. senegal (343 g kg-1 DM) and lowest in A. compylacantha (151 g kg-1 DM). There was no significant difference (P[0.05) in the gas kinetics and total volume of gas produced by the browse species.
Keywords: Browse species; Pastoral; Drylands; Nutritive value; Goats